Investigation into different approaches in the fight against antimicrobial resistance: studying the microbiome using human gastric organoids, bioinformatic analysis of a hospital outbreak and predatory bacteria as a therapeutic - Ford, Rhian Marie (2021)
Antimicrobial resistance poses one of the greatest threats of modern times. The low estimate in 2014 of 700,000 deaths a year attributable to antimicrobial resistance is only set to increase. Discovery of novel antimicrobial compounds is a slow, expensive process resulting in a product designed to be used sparingly and for short time frames leading to many pharmaceutical companies scaling back their antimicrobial pipelines. Antimicrobial resistance, however, can occur rapidly and spread across species to disseminate throughout the world at a rate faster than we can control. As such research is desperately needed not only into novel antimicrobial compounds themselves but alternative approaches to fight the increasing prevalence of resistant organisms. These approaches include but are not limited to (i) expanding our understanding of microbes and the different environments they inhabit, (ii) using bioinformatic tools to better track the spread of resistance genes over time or during outbreaks, (iii) altering materials or the microbiome to disrupt pathogenic microbes, or (iv) using microbes themselves to inhibit, compete or even ingest harmful pathogens. In this thesis I will discuss the challenge of antibiotic resistance and the approaches to combat resistance that I have learnt about during my training year. Firstly, looking at the role that the microbiome has on host signalling during infection with the globally prevalent bacterium Helicobacter pylori. Secondly, I will use bioinformatic tools to investigate the genomic data of an outbreak of multidrug resistant Acinetobacter baumanii across a UK hospital, determining which cases likely belong to the outbreak, data the original investigators used to determine where cross infection was occurring. Finally, I will discuss my plans for a project investigating the role of polyamines in the life of the predatory bacterium Bdellovibrio bacteriovorus, the proposed ‘living antibiotic’.